The influence of drug physicochemical properties on release from thermoresponsive smart hydrogels - Coughlan, David C. (Trinity College (Dublin, Ireland). School of Pharmacy & Pharmaceutical Sciences, 2005)
Thermoresponsive hydrogels are a class of "smart" or "environmentally sensitive" systems with potential for controlling the release of a drug in response to a specific stimulus. Previous research in the area of thermoresponsive drug delivery did not examine the effect of the chosen drug on the release pattern obtained. The potential use of thermoresponsive poly(N-isopropylacrylamide) hydrogels was evaluated in the present thesis by using a range of model drugs with different physicochemical properties. The characteristics of the drugs used and their effects on the "smart" behaviour of thermoresponsive hydrogels were investigated. Drug release profiles were examined above and below the phase transition temperature of the hydrogels. The drug release mechanism during the hydrogel swelling period was approximately diffusion controlled, with some contribution from the swelling process. The swelling process had a greater effect on the release mechanism of the smaller model drugs. It was shown that it was possible to alter the mechanism (from Fickian to non-Fickian) and release rate of a drug by changing the drug loading or the crosslinking content of the hydrogel, where the swelling characteristics and therefore pore size of the hydrogel was affected.
Keywords: Pharmaceutics, Ph.D.; Ph.D. Trinity College Dublin